Based on the shape of the frontal surface of the column of the working body of the chisel-cultivator (Journal of Architectural Design, 2022)
In this article was revised theoretical research forms of stand on agro- energetical indicators of chisel cultivator’s work. For exception of clogging up of stands with plant remainders it is important to change their configuration, so that the opportunity of stand self-cleaning from plant remainders during the work itself would appear. In order to find optimal forms of cross cut there was studied different existing and experimental forms of stand frontal covers. The conducted researches show that asymmetrical frontal cover of stand better cleans from litter, and notably decreases the traction resistance of soil.